Evaluasi Kesesuaian Lahan untuk Kawasan Industri di Wilayah Pengembangan Industri Kabupaten Karawang - Aryati, Ria, Dr. Kuswaji Dwi Priyono, M.Si, Ir. Taryono, M.Si (2017)
The purpose of this research is to determine the suitability level of the land for an industrial estate in Karawang regency, and to know the characteristics of the land suitable for determination of an industrial estate locations in Karawang regency. The location of the study area is limited to the area of industrial development that has been set in the RTRW Karawang. The research method used is the weighted tiered quantitative method, which each parameter is given the dignity and weight according to the great influence that owned to get the level of industrial land suitability. The process of data acquisition and data processing are carried out by using remote sensing data and GIS applications, while the technique of sampling using purposive sampling. This study uses two remote sensing data that are Quickbird Imagery and Landsat 8 Imagery. Quickbird Imagery is used to obtain the information of land usage while Landsat 8 is used to obtain the information of landform. Based on the results of data processing, industrial development area in Karawang regency has 5 levels of land suitability that are very suitable, moderate suitable, marginally suitable, not suitable current and not suitable permanent. Land in the area of industrial development has largely marginal suitability level with an area of 391.85 km2, or 66.93% of the total area of industrial development. The level of the classification is also available on a wide area, namely 26.38 % or an area of 154.44 km2. Land with quite appropriate classification is largely located in District Cikampek and Ciampel. Land with a very appropriate classification has a very small area that is equal to 1.44 % or an area of 8.43 km2. Land classified as not suitable permanent is only found in the District of Ciampel with an area of 0.27 km2 or 0.05 %, while the land with no appropriate classification currently has an area of 5.21 % or of 30.48 km2. Land characteristics of very suitable class for Industrial Estate in Karawang is a land with a slope that is flat or has ramps (0-8%), the soil bearing capacity of more than 2.75 kg / cm2, the depth of the soil water levels ranged from 1.5 to 10 m, the soil texture is medium to coarse, have excellent drainage conditions, has a low level of vulnerability to floods, and has a distance to the main road is less than 1500 meters.